Ultraviolet graphene ultranarrow absorption engineered by lattice plasmon resonance. (25th August 2021) - Yan, Zhendong; Lu, Xue; Du, Wei; Lv, Zhongquan; Tang, Chaojun; Cai, Pinggen; Gu, Ping; Chen, Jing; Yu, Zi
Abstract: We numerically demonstrate an ultraviolet graphene ultranarrow absorption in a hybrid graphene-metal structure. The full-width at half maximum of the absorption band being 9 nm in ultraviolet range is achieved based on the coupling of lattice plasmon resonances of the metallic nanostructure to the optical dissipation of graphene. The position, absorbance and linewidth of the hybridized narrow resonant mode tuned by controlling geometrical parameters and materials are systematically investigated. The proposed structure possesses high refractive index sensitivity of 288 nm/RIU and figure of merit of 72, and can also be used to detect small molecules layer of sub-nanometer thickness and refractive index with small changes, providing promising applications in ultra-compact efficient biosensors.